12th IFIP/IEEE International Symposium on Integrated Network Management (IM 2011) and Workshops 2011
DOI: 10.1109/inm.2011.5990518
|View full text |Cite
|
Sign up to set email alerts
|

On the design of a flexible software platform for in-building OTT service provisioning

Abstract: Abstract-We propose a software platform which pairs context awareness with over-the-top (OTT) service deployment. By augmenting OTT services with local context information, we allow them to react upon various types of changes in the environment in which they are being deployed. This lets service providers offer more personalized and fine-grained applications, while making use of a third-party infrastructure, via the OTT paradigm.Through UML diagrams, we describe the architecture of the proposed service platfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In previous work, we showed that the machines are capable of performing common ontological reasoning tasks. [16] WiLab's large number allowed us to run simulations in parallel.…”
Section: A Evaluation Methodologymentioning
confidence: 99%
“…In previous work, we showed that the machines are capable of performing common ontological reasoning tasks. [16] WiLab's large number allowed us to run simulations in parallel.…”
Section: A Evaluation Methodologymentioning
confidence: 99%
“…Thus, implicitly, at least two symbiotic networks are formed. In [2], we described a software architecture to enable such a context-aware over-the-top service platform, thereby presenting initial steps toward answering research question 5. It is displayed in Fig.…”
Section: Approachmentioning
confidence: 99%
“…Initial benchmarks on WiLab have yielded favorable results, but further experimentation is needed. [2] We are still in the early stages of researching dynamic service composition. The body area network scenario will therefore be addressed further when we have sufficiently researched the case of mostly static in-building services.…”
Section: Approachmentioning
confidence: 99%